Doping of polyaniline by corona discharge - Job, A. E.; Giacometti, J. A.; Herrmann, PSP; Mattoso, LHC (American Institute of Physics (AIP), 2000)
In the present article it is shown that a corona discharge can be employed to dope thin films of polyaniline (PANI) coated on poly(ethylene terephthalate) films, allowing the electrical conductivity to be tuned within the range 10(-10) to 0.3 S cm(-1). A study of the effect of different corona conditions, namely corona treatment for positive and negative polarities, air humidity, treatment time, corona current, and the geometry of the corona triode, on the electrical conductivity of the polyaniline is presented. The results indicate that the corona discharge leads to protonic doping of polyaniline similar to that which occurs in conventional protonic acid solution doping. Atomic force microscopic analysis shows that, as the PANI is exposed to the corona discharge, its globular morphology is disrupted leading to the appearance of droplet-like features and a significant decrease in the average height and surface roughness. Doping by corona discharge presents several advantages over the conventional solution method namely that it is a dry process which does not require use of chemicals reagents, and which is both rapid and avoids dopant migration. The latter can be important for applications of PANI in microelectronic devices. (C) 2000 American Institute of Physics. [S0021-8979(00)01608-X].